Knowledge and perception regarding the issues, opportunities and practices of public health among Ayurveda interns in India (South East Asia Journal of Public Health, 2014)
South East Asia Journal of Public Health 2013; 3(1): 74-76 DOI: http://dx.doi.org/10.3329/seajph.v3i1.17717